Cuentas por cobrar de la empresa All Plastic S.A. Plactisa de la ciudad de Guayaquil durante los períodos 2022 - 2023. - García Cervantes, Keren Mayling (2023)
The present case study titled accounts receivable in the company All Plastic S.A (PLACTISA), located in the city of Guayaquil, during the periods 2022-2023, the main objective is to examine the management of the company's accounts receivable, to identify the impact on the company's liquidity, for this, a financial analysis was carried out based on key indicators such as the average collection period, delinquency rate and turnover of accounts receivable. The company's financial statements were examined and interviews were conducted with personnel in charge of credit and collection management. The results showed that the company faces certain challenges in portfolio recovery, which affects its cash flow and investment capacity. Delays in customer payments, flexible credit policies and the need to improve collection procedures were identified. As part of the conclusions and recommendations, it was suggested to implement a risk control system for the processes that are executed regarding accounts receivable that allows liquidity problems to be identified in advance in order to correct errors in a timely manner.